Factors related to the development of health-promoting community activities in Spanish primary healthcare: two case–control studies. Issue 10 (8th October 2017) - March, Sebastià; Ripoll, Joana; Jordan Martin, Matilde; Zabaleta-del-Olmo, Edurne; Benedé Azagra, Carmen Belén; Elizalde Soto, Lázaro; Vidal, Mª Clara; Bauzà Amengual, María de Lluc; Planas Juan, Trinidad; Pérez Mariano, Damiana Maria; Llull Sarralde, Micaela; Ruiz-Giménez, Juan Luís; et al.
Abstract : Objective: Spanish primary healthcare teams have the responsibility of performing health-promoting community activities (CAs), although such activities are not widespread. Our aim was to identify the factors related to participation in those activities. Design: Two case– control studies. Setting: Performed in primary care of five Spanish regions. Subjects: In the first study, cases were teams that performed health-promoting CAs and controls were those that did not. In the second study (on case teams from the first study), cases were professionals who developed these activities and controls were those who did not. Main outcome measures: Team, professional and community characteristics collected through questionnaires (team managers/professionals) and from secondary sources. Results: The first study examined 203 teams (103 cases, 100 controls). Adjusted factors associated with performing CAs were percentage of nurses (OR 1.07, 95% CI 1.01 to 1.14), community socioeconomic status (higher vs lower OR 2.16, 95% CI 1.18 to 3.95) and performing undergraduate training (OR 0.44, 95% CI 0.21 to 0.93). In the second study, 597 professionals responded (254 cases, 343 controls). Adjusted factors were professional classification (physicians do fewer activities than nurses and social workers do more), training in CAs (OR 1.9, 95% CI 1.2 to 3.1), team support (OR 2.9, 95% CI 1.5 to 5.7), seniority (OR 1.06, 95% CI 1.03 to 1.09), nursing tutor (OR 2.0, 95% CI 1.1 to 3.5), motivation (OR 3.7, 95% CI 1.8 to 7.5), collaboration with non-governmental organisations (OR 1.9, 95% CI 1.2 to 3.1) and participation in neighbourhood activities (OR 3.1, 95% CI 1.9 to 5.1). Conclusions: Professional personal characteristics, such as social sensitivity, profession, to feel team support or motivation, have influence in performing health-promoting CAs. In contrast to the opinion expressed by many professionals, workload is not related to performance of health-promoting CAs.